PERTUMBUHAN TUNAS ANGGUR HITAM (Vitis vinifera L.) PADA BERBAGAI KONSENTRASI BENZYLAMINO PURIN DAN INDOLEBUTYRIC ACID - Mardiyah Mardiyah; Zainuddin Basri; Ramal Yusuf; Hawalina Hawalina (Universitas Tadulako, 2017)
This study aimed to determine media compositions supplied with BAP and IBA suitable for the growth of black grape shoots. This research was conducted at the Laboratory of Plant Biotechnology, Faculty of Agriculture, University of Tadulako, during April to September 2016. The study used a factorial completely randomized design. Two factors were tested, the concentrations of BAP i.e. 1.50 ppm, 2.00 ppm and 2.50 ppm; and the concentration of IBA i.e. 0.00 ppm, 0.25 ppm and 0.50 ppm. There were nine treatment combinations and each combination treatment was replicated three times to obtain 27 experimental units. Each experimental unit using an explant. Data were analyzed using analysis of variance and followed by Honestly Significant Difference test at level of 5% if the treatment effects were significant. The results showed that the composition of the culture media supplied with 2.00 ppm BAP without IBA is able to stimulate the formation of black grape leaves at the earliest, at an average of 18.67 days per explant, while the media added with 2.00 ppm 0.25 ppm BAP together with IBA can lead to longest shoot growth, at an average of 2.13 cm per bud. The culture media applied with 2.50 ppm BAP can trigger earliest shoot growth and highest number of leaf formation which were 11.11 days after culture and 2.44 leaves per explant. Earliest formation of black grape shoots of 11.89 days after culture is stimulated by the addition of 0.25 ppm IBA.